P866 Faecal microbiota in newly diagnosed Crohn's disease and its relation to treatment escalation. (16th January 2018) - Vatn, S; Karlsson, M C; Carstens, A; Detlie, T E; Ricanek, P; Bergemalm, D; Lindquist, C M; Jahnsen, J; Halfvarson, J; Casèn, C; Vatn, M H; ,
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory disease which can affect any part of the gastrointestinal tract. The treatment aims at inducing and maintaining remission based on clinical symptoms, endoscopic appearance and biochemical markers. Some patients have a mild disease course whilst other develop a refractory disease or complicated disease behaviour, due to a stricturing/penetrating phenotype, leading to treatment escalation. Tools for predicting the disease course are limited. Identification of microbiota signatures, might be a tool for identification of patient with a poor prognosis and need of treatment escalation. Methods: Fecal samples were obtained at diagnosis from 33 newly diagnosed CD patients in the IBD- character cohort. Fecal microbiota composition was assessed using the GA-map™ Dysbiosis Test [Casén et al., 2015]. Disease course and treatment were followed up to 5 years after inclusion. The cohort was divided in two groups, one with a milder course and another with more severe disease progression demanding treatment escalation, defined by introduction of biologic treatment and/or surgery after initial treatment. Comparisons between the groups were made using the Wilcoxon test. Results: Among 33 CD patients, 28 (85%) were classified as dysbiotic (11 mild and 17 severe). A total of 12 (36%) patients required treatment escalation. At the time of diagnosis, the dysbiosis index, did not discriminate between patients who did or did not require treatment escalation. Akkermansia muciniphila was found to be reduced in CD patients who required treatment escalation compared with those who did not ( p = 0.04), while a component of unclassified Clostridiales was found to be significantly increased in CD patients who required treatment escalation ( p = 0.03). Conclusions: CD patients with an aggressive disease course exhibited a decreased abundance of Akkermansia muciniphila and an increased abundance of Clostridiales already at diagnosis. Our results might point to the relevance of these taxa for the discovery of predictive biomarkers that can be used to support tailored treatment in CD.